Fiscal decentralization, institutional quality, and government size: an asymmetry analysis for Asian economies. Issue 3 (3rd July 2022) - Sohail, Sidra; Ullah, Sana; Javid, Attiya Yasmin
Abstract: This study aims to examine the asymmetric effects of fiscal decentralisation and institutional quality on government size for selected Asian economies. The study employs asymmetric autoregressive distributed lag (ARDL) methodology by using time series data ranging from the period 1984 to 2017. The results show that positive shocks in expenditures decentralisation (ED) enhance government size in Japan, Kazakhstan, Thailand, Turkey, and reduces it in Korea, Rep. in the long-run. While negative shock in ED reduces government size in Pakistan, Thailand, Turkey and increases it in Kazakhstan and Mongolia in the long-run. Whereas asymmetric results in the long-run show that a positive shock in revenue decentralisation (RD) increases government size in Pakistan, Japan, Kazakhstan, Thailand, and Turkey, and a negative shock in RD decreases government size in Pakistan, Mongolia, Thailand, and Turkey. Our asymmetric results of institutional quality are also country-specific.